Student’s Perspective: Google Classroom Application in Learning English during the Pandemic - Ishak Ishak; Euis Yanah Mulyanah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This research aims to analyze students' perspectives by using the Google Classroom application in learning English during the pandemic. The subjects of this study were students from class XII IPS 3 at SMA Yuppentek 1 Kota Tangerang in the academic year 2021/2022. The research used a descriptive qualitative method. In collecting data, the author used 2 techniques, namely; interviews and questionnaires. The results of this study are based on their perspective, it can be concluded that online learning is fun. Learning online is more relaxed because it can be done anywhere. Online learning makes saving time and money. Students also study online due to pandemic conditions that require them to study online. However, the negative side of online learning is unstable network conditions, sometimes constrained by the internet quota being exhausted, unfocused, and less effective in delivering subject matter which ultimately makes it difficult for students to understand the subject matter and using Google Classroom facilitated the online learning process during the Covid-19 pandemic, but there is no denying that they also consider face-to-face learning to be more effective than online learning.